Evaluating the environmental performance of a product/service-system business model for Merino wool next-to-skin garments: The case of Armadillo Merino® - Bech, Nynne Marie; Birkved, Morten; Charnley, Fiona; Laumann Kjaer, Louise; Pigosso, Daniela C. A.; Hauschild, Michael Z.; McAloone, Tim C.; Moreno, Mariale (MDPI, 2019)
Circular business models are often enabled by means of product/service-systems (PSS). The common perception is that such business models have enhanced environmental performance when compared to conventional business models rooted in the linear economy. This article investigates the environmental potential of developing a use-oriented PSS business model for Merino wool t-shirts intended for use by the British Ministry of Defence as an alternative to the present supply system based on synthetic t-shirts purchased from sportswear clothing companies. To conduct the assessment, we apply the life cycle assessment (LCA) methodology to quantify and compare the climate change impacts and impact potentials of the proposed PSS business model and of a reference business model. Results showed that there could be significant contribution of quantifying environmental potential for PSS business models when justifying the transition to a circular economy. However, when adopting LCA methodology for this purpose, the design of the PSS needs to be well thought to overcome some of the identified challenges. The article concludes by making the case that LCA studies can support the definition, design and value creation of the product/service-systems in early development stages.
Keywords: product service system; PSS; circular economy; LCA; merino wool